Training leading to repetition failure enhances bench press strength gains in elite junior athletes - Drinkwater, E. J.; Lawton, T. W.; Lindsell, R. P.; Pyne, D. B.; Hunt, P. H.; McKenna, M. J. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to investigate the importance of training leading to repetition failure in the performance of 2 different tests: 6 repetition maximum (6RM) bench press strength and 40-kg bench throw power in elite junior athletes. Subjects were 26 elite junior male basketball players (n = 12; age = 18.6 ± 0.3 years; height = 202.0 ± 11.6 cm; mass = 97.0 ± 12.9 kg; mean ± SD) and soccer players (n = 14; age = 17.4 ± 0.5 years; height = 179.0 ± 7.0 cm; mass = 75.0 ± 7.1 kg) with a history of greater than 6 months' strength training. Subjects were initially tested twice for 6RM bench press mass and 40-kg Smith machine bench throw power output (in watts) to establish retest reliability. Subjects then undertook bench press training with 3 sessions per week for 6 weeks, using equal volume programs (24 repetitions × 80-105% 6RM in 13 minutes 20 seconds). Subjects were assigned to one of two experimental groups designed either to elicit repetition failure with 4 sets of 6 repetitions every 260 seconds (RF4×6) or allow all repetitions to be completed with 8 sets of 3 repetitions every 113 seconds (NF8×3). The RF4×6 treatment elicited substantial increases in strength (7.3 ± 2.4 kg, +9.5%, p < 0.001) and power (40.8 ± 24.1 W, +10.6%, p < 0.001), while the NF8×3 group elicited 3.6 ± 3.0 kg (+5.0%, p < 0.005) and 25 ± 19.0 W increases (+6.8%, p < 0.001). The improvements in the RF4×6 group were greater than those in the repetition rest group for both strength (p < 0.005) and power (p < 0.05). Bench press training that leads to repetition failure induces greater strength gains than nonfailure training in the bench press exercise for elite junior team sport athletes.